ELECTRIC BICYCLE SELECTION SYSTEM USING MULTI CRITERIA DECISION MAKING - Heribertus Ary Setyadi; Doddy Satrya Perbawa (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
Indonesia government has targeted that by 2025 electric vehicle production has reached 20%. Many electric bicycle products have been sold and used in Indonesia, both domestically made and imported. The most important technical considerations in choosing an electric bicycle are battery type and motor used. These two components affect distance traveled by electric bicycles even further. Many brands offered by manufacturers with various advantages and disadvantages will make consumers are confused about choosing a quality and durable electric bicycle. From these problems, one solution is to create a mobile-based decision support system (DSS) that can assist in making decisions according to predetermined criteria. This research aims to produce recommendations for electric bicycle brands that can assist potential consumers in choosing electric bicycles. The combination of the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods is used in order to produce more objective recommendations. In this research uses seven criteria that will be processed in AHP, namely price, maximum load, battery capacity, motor power, charging time, mileage and speed. There are nine brands that are used as alternatives in the TOPSIS calculation. From AHP and TOPSIS calculation, following recommendations for electric bicycles is obtained: the first order is the Ofero with a preference value of 1, next order are with the same value 0.5806, Indobike and Exotic, and the last recommendation is Jarvis with a value of 0.095.